Data from: The first set of universal nuclear protein-coding loci markers for avian phylogenetic and population genetic studies - Liu, Yang; Liu, Simin; Yeh, Chia-Fen; Zhang, Nan; Chen, Guoling; Que, Pinjia; Dong, Lu; Li, Shou-hsien (Dryad, 2018)
Multiple nuclear markers provide genetic polymorphism data for molecular
systematics and population genetic studies. They are especially required
for the coalescent-based analyses that can be used to accurately estimate
species trees and infer population demographic histories. However, in
avian evolutionary studies, these powerful coalescent-based methods are
hindered by the lack of a sufficient number of markers. In this study, we
designed PCR primers to amplify 136 nuclear protein-coding loci (NPCLs) by
scanning the published Red Junglefowl (Gallus gallus) and Zebra Finch
(Taeniopygia guttata) genomes. To test their utility, we amplified these
loci in 41 bird species representing 23 Aves orders. The sixty-three
best-performing NPCLs, based on high PCR success rates, were selected
which had various mutation rates and were evenly distributed across 17
avian autosomal chromosomes and the Z chromosome. To test phylogenetic
resolving power of these markers, we conducted a Neoavian phylogenies
analysis using 63 concatenated NPCL markers derived from 48 whole genomes
of birds. The resulting phylogenetic topology, to a large extent, is
congruence with results resolved by previous whole genome data. To test
the level of intraspecific polymorphism in these makers, we examined the
genetic diversity in four populations of the Kentish Plover (Charadrius
alexandrinus) at 17 of NPCL markers chosen at random. Our results showed
that these NPCL markers exhibited a level of polymorphism comparable with
mitochondrial loci. Therefore, this set of pan-avian nuclear
protein-coding loci has great potential to facilitate studies in avian
phylogenetics and population genetics.
alignments of universal nuclear protein-coding loci and Perl script for
BLAST1. Alignment of 48species at 65genes; 2. Alignment of the four
populations of Kentish Plover at 19 genes; 3. Partition of 48species at 65
genes; 4. Partition of the four populations of Kentish Plover at 19 genes;
5.Perl Script for BLASTDRYAD_NPCL_Data.zip
Keywords: multiple bird species